Synchronization of Chaotic Semiconductor Lasers with Optoelectronic Feedback and its Applications to Encoded Communications - Tahir, Fadil Rahma (Basrah Journal for Engineering Sciences, 2006)
The theoretical study of synchronization of two coupled single mode semiconductor lasers is achieved. The transmitter is laser subject to optoelectronic feedback that operates in a chaotic regime. The receiver can also operate in a chaotic regime similar to the transmitter. The effects of parameter mismatch on the synchronization of two lasers with optoelectronic feedback are determined, with mismatch in delay time, with mismatch in feedback strength, and with coupling strength between two systems. The synchronization is sensitive to mismatch in the delay time for the transmitter and receiver feedback loops. An open - loop receiver configuration does not have the problem of delay time mismatch and shows the highest synchronization. The synchronization phenomena that appear in the two-coupled semiconductor lasers can be used in communications systems. Finally, an encoding and decoding of message on the chaotic carrier is demonstrated.